T-shirts For College Bound Students: A School-University Service-Learning Project - Kathryn Wallert; Beth Walizer (The Advocate, 2015)
This paper explores how service-learning projects provide university students experiential learning opportunities to participate in innovative activities. While educating and fostering development through mentoring and teamwork, university students enhanced critical thinking and interpersonal skills, gained background knowledge of the elementary school, implemented the project, reflected on their experiences, and evaluated the project. The project encouraged elementary students to achieve their goals by instilling the expectation of furthering a higher education after secondary school. In addition to providing a service to the children, university students identified through their reflections the connection between their service and what they have acquired academically.